2015
DOI: 10.1073/pnas.1520947112
|View full text |Cite
|
Sign up to set email alerts
|

Human autoreactive T cells recognize CD1b and phospholipids

Abstract: In contrast with the common detection of T cells that recognize MHC, CD1a, CD1c, or CD1d proteins, CD1b autoreactive T cells have been difficult to isolate in humans. Here we report the development of polyvalent complexes of CD1b proteins and carbohydrate backbones (dextramers) and their use in identifying CD1b autoreactive T cells from human donors. Activation is mediated by αβ T-cell receptors (TCRs) binding to CD1b-phospholipid complexes, which is sufficient to activate autoreactive responses to CD1b-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 39 publications
4
101
1
Order By: Relevance
“…Recent studies that identified lipid autoantigens in vitro pointed to candidate self-lipids that might function in this in vivo disease, including cholesterol (31), fatty acids (17), and membrane phospholipids (19,45). To identify self-lipids presented by CD1b to HJ1 T cells, CD1b plate-bound assays were performed.…”
Section: The Expression Of Costimulatory Molecule Cd86 On Cd1b-expresmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies that identified lipid autoantigens in vitro pointed to candidate self-lipids that might function in this in vivo disease, including cholesterol (31), fatty acids (17), and membrane phospholipids (19,45). To identify self-lipids presented by CD1b to HJ1 T cells, CD1b plate-bound assays were performed.…”
Section: The Expression Of Costimulatory Molecule Cd86 On Cd1b-expresmentioning
confidence: 99%
“…A recent study also demonstrated that CD1a-restricted T cells responded to neolipid antigens generated by phospholipase A 2 activity in psoriasis patients (30). CD1b-autoreactive T cells can recognize phospholipids (17,19), and a higher frequency of sulfatide and monosialotetrahexosylganglioside-specific (GM1-specific) T cells was detected in multiple sclerosis patients compared with normal controls (26). Moreover, CD1c-restricted T cells specific for cholesteryl esters have recently been identified (31).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…29 In addition, recent studies have shown that CD1a-restricted human T cell clones recognize skin-derived apolar oils and phospholipids; autoreactive CD1b-restricted human T cell clones recognize a range of phospholipids, whereas CD1c-reactive clones can bind cholesterol and its esters. [31][32][33] Considering that these lipids accumulate in most tumors, it is imperative to explore the role of autoreactive group 1 CD1-restricted T cells in tumor immunity. This would shed light on the potential use of these T cells in cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, some self-reactive T cells also display cross-reactivity for microbial antigens (Table 1). In PNAS, Van Rhijn et al define the cross-reacting bacterial and self-antigens of a group of T lymphocytes that respond to antigens bound to or presented by CD1b (1). Their findings suggest one mechanism whereby dangerous, CD1-mediated self-reactivity by T cells might be controlled, and the authors provide a hypothesis for why cross-reactive recognition of the antigens they define might be useful.…”
mentioning
confidence: 99%